Femoral osteotomy to improve range of motion in residual deformity of perthes disease: A case report. (July 2020) - Matsubayashi, Shohei; Chiba, Ko; Tsujimoto, Ritsu; Osaki, Makoto; Wada, Akifusa
Abstract: Introduction: The treatment strategies for residual deformity of Perthes disease are not established. Case presentation: This is a case report of a 15-year-old boy. He developed right Perthes disease (lateral pillar classification group B) when he was 10 years old and underwent varus femoral osteotomy of the right side. At 12 years of age, he developed left Perthes disease (lateral pillar classification group B) and underwent varus femoral osteotomy of the left side. Postoperatively, he was treated with partial weight bearing of the left leg with crutches. At 15 years, range of motion (ROM) of his left hip was markedly limited at 30° flexion, 10° abduction, 70° external rotation, and −20° internal rotation, and he was having difficulty maintaining a sitting position. Diagnosis: Stulberg group V was noted on plain radiography. Computed tomography (CT) showed collapse of the load-bearing part of the femoral head on the coronal plane, but the ball-shape was maintained in the posterior femoral head on sagittal and transverse sections. Intervensinos: Valgus-flexion-internal rotation osteotomy was performed to improve ROM. Outcomes: Left hip ROM improved to 90° flexion, 20° abduction, 50° external rotation, and 40° internal rotation immediately after the surgery. He was able to sit 10 months postoperatively but was left with a limp and limited ROM in the left hip at 60° flexion. Chondroplasty was performed during the plate removal surgery at 10 months postoperatively, which improved hip flexion to 100° immediately after the surgery. The patient was left with limited ROM of 60° flexion of the left hip at the final observation. Conclusion: Femoral osteotomy to improve ROM could be an option for residual deformity of Perthes disease. Highlights: Treatment strategies for residual deformity of Perthes disease after skeletal maturity are not established. Soft tissues must also be altered to achieve ROM. Valgus-flexion-internal rotation osteotomy was performed as salvage operation for residual deformity of Perthes disease and improved ROM.